2011
DOI: 10.1124/mol.111.074302
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Molecular Mechanism of the α7 Nicotinic Acetylcholine Receptor Positive Allosteric Modulator PNU-120596 Provides Evidence for Two Distinct Desensitized States

Abstract: Although ␣7 nicotinic acetylcholine receptors are considered potentially important therapeutic targets, the development of selective agonists has been stymied by the ␣7 receptor's intrinsically low probability of opening (P open ) and the concern that an agonist-based therapeutic approach would disrupt endogenous cholinergic function. Development of ␣7 positive allosteric modulators (PAMs) holds promise of avoiding both issues. N-(5-Chloro-2,4-dimethoxyphenyl)-NЈ-(5-methyl-3-isoxazolyl)-urea (PNU-120596) is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
212
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 101 publications
(229 citation statements)
references
References 39 publications
16
212
1
Order By: Relevance
“…1E is a single-channel recording of ␣7 receptor currents in the presence of 10 M GAT107. Bursting activity was observed that was similar to that reported for ACh and PNU-120596 (10).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…1E is a single-channel recording of ␣7 receptor currents in the presence of 10 M GAT107. Bursting activity was observed that was similar to that reported for ACh and PNU-120596 (10).…”
Section: Resultssupporting
confidence: 72%
“…The binding of orthosteric agonists alone promote only rare and brief openings, although orthosteric agonists with the PAMs also bound produce occasional protracted bursts of openings occurring from a PAM-sensitive desensitized state (D s ) (10). Shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations